SOCIETY DIMENSIONS REVIEWED FROM LOSS & GRIEVING IN COVID-19 PANDEMIC ERA - Rahmawati Rahmawati; Evita Muslima Isnanda Putri; Fidrotin Azizah (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Covid-19 pandemic has spread across the world and is having an impact globally. The rules for handling the Covid-19 pandemic force people to change their habits and patterns of daily life. Covid-19 has brought dramatic changes to our lives, including many losses. However, change or transition experienced by the community due to the Covid-19 pandemic can cause loss and grief (Rosyanti&Hadi, 2020). Objectives: This study aims to determine society dimension variables with loss and grief in Covid-19 pandemic era. Methods: Correlational analytic with cross sectional approach. A sample of 278 respondents with accidental sampling technique. The instrument used a questionnaire distributed by social media which included data on community dimensions and instrument loss and grieving community facing the Covid-19 pandemic. The validity and reliability of the research instrument were tested using the Cronbach's Alpha test. Descriptive analysis with process analysis, analytic analysis with chi square test and Spearman's Rho at a significance level of 5%. Results: Based on age, adolescence to early adult are mostly in the anger stage (33.3%), adult and the elderly range are in the Bargaining stage (50.76-70%). Based on gender, male (48.4%) and female (57.2%) are in the Bargaining stage. Based on the education: basic until higher education, more than half of them are in the Bargaining stage (42.8-54.4%). Based on occupation, most respondents who do not work are in the anger stage (50%) government employees, general employees, self-employed and still in school are in the Bargaining stage (47.2-61.8%). Conclusion: The length of time the incident occurred, the cultural context, the similarity of policies, and the territorial background of the Indonesian State greatly influenced the loss and grieving stages, making the majority of the grieving stages in the Bargaining stage.